Identification of novel efflux pump inhibitors for Neisseria gonorrhoeae via multiple ligand-based pharmacophores, e-pharmacophore, molecular docking, density functional theory, and molecular dynamics approaches. (June 2022) - Jain, Neha; Sk, Md Fulbabu; Mishra, Amit; Kar, Parimal; Kumar, Amit
Abstract: Neisseria gonorrhoeae have progressively developed resistance to almost all antibiotics, and it has become imperative to develop novel approaches to combat its multi-drug resistance. Overexpression of the MtrCDE, an RND family efflux pump, is one of the primary causes of antibiotic resistance in the gonococcus and is considered an important target for combating anti-microbial resistance. PaβN, D13–9001, and other EPIs are identified to target the RND efflux pumps, but due to their cytotoxicity, they have failed in clinical trials. Herein, an extensive pharmacophore-based approach was performed to identify novel EPI inhibitors with improved pharmacology/safety profiles. An integrated computational framework comprising pharmacophore generation, virtual screening using HTVS, SP and XP Glide methodology, MM-GBSA analysis, Induced fit docking, QPLD, DFT, ADMET properties calculation, Molecular Dynamics, and MM-PBSA analysis was performed. The comprehensive study leads to the identification of five non-toxic bioactive compounds, namely - ZINC000008764610, ZINC000030879142, ZINC000030879358, ZINC000253414904, and ZINC000225394671, as potential EPIs for RND efflux pump of Neisseria gonorrhoeae . The five compounds were selected based on the pharmacophore mapping, higher dock score than the known EPIs, binding stability, molecular interactions with the critical residues of MtrD protein, higher ADMET properties, non-toxicity, and free energy estimations. In summary, the analysis led to the identification of five top hits from the natural compound subset of the ZINC database that has a higher binding affinity to the MtrD and adequate physiochemical/pharmacokinetic profile that can be used for the generation of novel EPIs against Neisseria gonorrhoeae . Graphical Abstract: ga1 Highlights: Neisseria gonorrheae have shown high multi-drug resistance & needs to be tackled on urgent basis. Efflux pumps are novel drug targets that can potentiates the use of antibiotics against pathogens. An extensive pharmacophore based screening was performed to identify novel EPIs for N. gonorrheae . The lead molecules showed strong binding interactions with the active-site residues of MtrD Ng . These lead molecules can be used to develop therapeutics for N. gonorrheae caused gonorrhea.